Innovative Methods and Tools for Developing Students' Entrepreneurial Skills Using CLIL Technologies - Madaminjonovna, Mirzakarimova Makhliyokhon (International Journal on Human-Computing Studies, 2023)
This article discusses the idea that students should be active participants in the learning process from a sluggish listener, based on entrepreneurial-oriented learning technologies. Innovative methods and tools for the development of students' entrepreneurial skills with the help of CLIL technologies were analyzed.